2009
DOI: 10.1111/j.1365-2958.2009.06647.x
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of a fungal virulence factor reveals structural homology with mammalian saposin B

Abstract: SummaryThe fungal protein CBP (calcium binding protein) is a known virulence factor with an unknown virulence mechanism. The protein was identified based on its ability to bind calcium and its prevalence as Histoplasma capsulatum's most abundant secreted protein. However, CBP has no sequence homology with other CBPs and contains no known calcium binding motifs. Here, the NMR structure of CBP reveals a highly intertwined homodimer and represents the first atomic level NMR model of any fungal virulence factor. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 50 publications
0
24
2
Order By: Relevance
“…Although it is completely unknown how C. albicans causes incomplete phagosome maturation, it has been suggested that H. capsulatum and Cr. neoformans secrete proteins and polysaccharides that lead to the formation of abnormal phagosomes (65)(66)(67). A. fumigatus possesses a surface-bound structure (1,8-dihydroxynaphthalene-like melanin) that has been proposed to inhibit lysosomal fusion in human MDMs (68).…”
Section: Glabrata Blocks Phagolysosome Formation and Phagosome Acimentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is completely unknown how C. albicans causes incomplete phagosome maturation, it has been suggested that H. capsulatum and Cr. neoformans secrete proteins and polysaccharides that lead to the formation of abnormal phagosomes (65)(66)(67). A. fumigatus possesses a surface-bound structure (1,8-dihydroxynaphthalene-like melanin) that has been proposed to inhibit lysosomal fusion in human MDMs (68).…”
Section: Glabrata Blocks Phagolysosome Formation and Phagosome Acimentioning
confidence: 99%
“…Both species block the fusion of phagosomes with lysosomes, as lysosomal membrane proteins are actively recycled from, and hydrolytic compounds are reduced in, their phagosomes. In the case of H. capsulatum, it is known that reduced accumulation of the phagolysosomal proton pump, vacuolar ATPase, together with the activity of the fungal saposin-like calcium-binding protein, which potentially interacts with host lipids of the phagosome, contributes to altered phagosome trafficking (18,65). As all anti-vacuolar ATPase Abs tested in this study (four in total) bound nonspecifically to the surface of C. glabrata cells (and were thus not suitable for microscopic analysis; data not shown), it remains unclear whether C. glabrata may prevent acidification by downregulation of vacuolar ATPase.…”
Section: Glabrata Blocks Phagolysosome Formation and Phagosome Acimentioning
confidence: 99%
“…Candida albicans expresses an integrin-like protein Int1p [42] that binds yeast to vascular endothelium and promotes filamentation and virulence [43], [44]. Histoplasma capsulatum CBP1, a virulence factor, is similar in its 3-D NMR structure to mammalian saposin B [45], but evidence of saposin-like interactions with host glycolipid has not yet been reported. We describe a striking example of molecular mimicry involving sequences in the BAD-1 tandem repeat that mimic those in mammalian TSP-1 structurally and functionally, and confer pathogen survival.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of Cbp1, Histoplasma yeast grow at a similar rate in culture; however, the yeast are attenuated in both macrophage and mouse assays of virulence (Sebghati , et al , 2000, Edwards , et al , 2011). While the exact mechanism of Cbp1 contribution to virulence remains unknown, the Cbp1 homodimer has structural similarity to mammalian saposin B (Beck , et al , 2009) suggesting a role in transforming the phagocytic compartment into a permissive environment for yeast survival and replication. The Cbp1 requirement for both G186A and G217B virulence indicates conservation of at least one mechanism for pathogenesis.…”
Section: Established Virulence Factorsmentioning
confidence: 99%